2017
DOI: 10.1038/s41598-017-03378-5
|View full text |Cite
|
Sign up to set email alerts
|

Look me in the eyes: constraining gaze in the eye-region provokes abnormally high subcortical activation in autism

Abstract: Individuals with Autism Spectrum Disorder (ASD) seem to have difficulties looking others in the eyes, but the substrate for this behavior is not well understood. The subcortical pathway, which consists of superior colliculus, pulvinar nucleus of the thalamus, and amygdala, enables rapid and automatic face processing. A specific component of this pathway – i.e., the amygdala – has been shown to be abnormally activated in paradigms where individuals had to specifically attend to the eye-region; however, a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 64 publications
4
106
1
1
Order By: Relevance
“…According to Tanaka and Sung [], eye contact is uncomfortable for people with ASD regardless of whether the face is neutral or emotional. However, when faces display a fearful expression, eyes could even be more arousing than when faces are neutral or expressing another emotion, as they signal the presence of an environmental threat, although our group recently reported the presence of an eye‐contact effect for all emotions in ASD [Hadjikhani et al, ]. Further supporting this hypothesis, it was shown that, contrary to controls, ASD participants reflexively shift their attention away from the eye region when perceiving emotional faces [Kliemann et al, ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…According to Tanaka and Sung [], eye contact is uncomfortable for people with ASD regardless of whether the face is neutral or emotional. However, when faces display a fearful expression, eyes could even be more arousing than when faces are neutral or expressing another emotion, as they signal the presence of an environmental threat, although our group recently reported the presence of an eye‐contact effect for all emotions in ASD [Hadjikhani et al, ]. Further supporting this hypothesis, it was shown that, contrary to controls, ASD participants reflexively shift their attention away from the eye region when perceiving emotional faces [Kliemann et al, ].…”
Section: Discussionmentioning
confidence: 80%
“…One study in which gaze was monitored during the presentation of face stimuli found that the extent to which ASD participants activate their social brain in response to observing emotional faces correlated to the amount of time they spent looking at the eyes [Dalton et al, ]. In addition, we have recently reported that constraining individuals with ASD to look in the eyes, compared with free‐viewing of dynamic emotional face stimuli, increases activation for all the emotions studied (neutral, happy, angry, and fear) in the subcortical face‐processing system, including the amygdala [Hadjikhani et al, ]. Since the eyes are highly important for decoding emotions [Smith and Schyns, ], the difficulties of people with ASD in accurately reading facial expressions could result from their lack of attention to the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings (Leekam, López, & Moore, ; Mundy, Sigman, & Kasari, ) suggest that a GF impairment may be most prominent early in development or in autistic children with lower mental age. Although it remains unclear to what extent GF is affected in ASD, different theories have been proposed to explain the impairment, including a diminished interest in faces and eyes (Chevallier, Kohls, Troiani, Brodkin, & Schultz, ); avoidance of eyes (Hadjikhani et al., ; but see Kylliäinen et al., ); impaired eye‐gaze direction detection (Forgeot d'Arc et al., ); and reinforcement learning differences (Triesch, Teuscher, Deák, & Carlson, ).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…[47] Functionally, hyperactivity of the amygdala has been reported in ASD populations during social tasks. [48] Unfortunately, very few imaging studies in humans have examined the amygdala at the level of its subdivisions, but one investigation of adults with ASD revealed complex patterns of atypical functional connectivity between various sub-regions of the amygdala and other brain regions. [42] 2.1.…”
Section: Mood Disorders and Amygdala Functionmentioning
confidence: 99%